Global importance of supporting the krill to whale component of the pelagic food web associated with migrations following deep sea seamounts - Bruce R. Hodgson (International Marine Science Journal, 2025)
The main diet of baleen whales is krill in the Arctic, Antarctic and during migrations in the Atlantic, Pacific and Indian Oceans. Hence, the aim of this paper is to quantify the global importance of the krill to baleen whale component of the pelagic food web and possible feedback loops. That was undertaken by comparing the results of Ecopath Models in the Antarctic and Arctic Oceans and to migration areas in the North Atlantic and Alaska, was well as the large Seamount area from the Antarctic and Arctic. Biological production transfer is the essential component of the prey to predator pelagic food web, which maintains the production of predators. The importance of sustaining global baleen whale migrations is to support ecosystem production by whale defecation contribution to nutrient recycling. It is important to sustain krill and fish abundance in whale migration feeding areas using ecosystem-based fishery management (EBFM) fishing rates. It was shown by the literature that migrations tended to followed deep-sea seamounts, and baleen whale defecation and nutrient cycling at seamounts led to the effects of nutrient upwelling by deep sea currents at seamounts. Hence, it is suggested seamounts be protected as important marine ecosystems. Therefore, those processes indicate sustaining krill and whale abundance is likely to support global marine ecosystem stability in open ocean migration areas.
Keywords: Whale krill consumption